Commentary on: Divalent metal cofactors differentially modulate RadA-mediated strand invasion and exchange in Saccharolobus solfataricus - Mangialavori, Irene Cecilia (2023)
RecA ATPases are a family of proteins that catalyzes the exchange of complementary DNA regions via homologous recombination. They are conserved from bacteria to humans and are crucial for DNA damage repair and genetic diversity. In this work, Knadler et al. examine how ATP hydrolysis and divalent cations impact the recombinase activity of Saccharolobus solfataricus RadA protein (ssoRadA). They find that the ssoRadA-mediated strand exchange depends on ATPase activity. The presence of Manganese reduces ATPase activity and enhances strand exchange, while calcium inhibits ATPase activity by preventing ATP binding to the protein, yet destabilizes the nucleoprotein ssoRadA filaments, allowing strand exchange regardless of the ATPase activity. Although RecA ATPases are highly conserved, this research offers intriguing new evidence that each member of the family requires individual evaluation.